The multifaceted consequences and economic costs of child anxiety problems: A systematic review and meta‐analysis - Jack Pollard; Tessa Reardon; Chloe Williams; Cathy Creswell; Tamsin Ford; Alastair Gray; Nia Roberts; Paul Stallard; Obioha C. Ukoumunne; Mara Violato (Wiley, 2023)
Abstract Background Over a quarter of people have an anxiety disorder at some point in their life, with many first experiencing difficulties during childhood or adolescence. Despite this, gaps still exist in the current evidence base of the multiple consequences of childhood anxiety problems and their costs. Methods A systematic review of Medline, PsycINFO, EconLit and the National Health Service Economic Evaluation Database was conducted for longitudinal and economic studies reporting on the association between childhood anxiety problems and at least one individual‐, family‐ or societal‐level outcome or cost. All studies were synthesised narratively. For longitudinal studies, 'effect direction' was used as a common metric, with random effects meta‐analysis undertaken where possible. Results Eighty‐three studies met inclusion criteria and were synthesised narratively. We identified 788 separate analyses from the longitudinal studies, which we grouped into 15 overarching outcome domains. Thirteen of the studies were incorporated into 13 meta‐analyses, which indicated that childhood anxiety disorders were associated with future anxiety, mood, behaviour and substance disorders. Narrative synthesis also suggested associations between anxiety problems and worse physical health, behaviour, self‐harm, eating, relationship, educational, health care, employment, and financial outcomes. 'Effect direction' was conflicting in some domains due to a sparse evidence base. Higher economic costs were identified for the child, their families, healthcare providers and wider society, although evidence was limited and only covered short follow‐up periods, up to a maximum of 2 years. Total annual societal costs per anxious child were up to £4040 (2021 GBP). Conclusions Childhood anxiety problems are associated with impaired outcomes in numerous domains, and considerable economic costs, which highlight the need for cost‐effective interventions and policies to tackle them. More economic evidence is needed to inform models of the long‐term, economic‐related, consequences of childhood anxiety problems.